2022
DOI: 10.3389/fcell.2022.770550
|View full text |Cite
|
Sign up to set email alerts
|

An Aging-Related Gene Signature-Based Model for Risk Stratification and Prognosis Prediction in Lung Squamous Carcinoma

Abstract: Aging is an inevitable process characterized by a decline in many physiological activities, and has been known as a significant risk factor for many kinds of malignancies, but there are few studies about aging-related genes (ARGs) in lung squamous carcinoma (LUSC). We designed this study to explore the prognostic value of ARGs and establish an ARG-based prognosis signature for LUSC patients. RNA-sequencing and corresponding clinicopathological data of patients with LUSC were downloaded from The Cancer Genome A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
2
8
1
Order By: Relevance
“…Furthermore, we compared the performance of the present signature with those of the other previously reported gene signatures in LUSC. The RMS curve showed that the performance of the present signature was similar to that of the other four signatures (Supplementary Figure S3C) (Huang et al, 2021;Li et al, 2022;Zhai et al, 2022). These results suggest that the CSRG signature can serve as a candidate prognostic biomarker for survival in patients with stage I-III LUSC.…”
Section: Internal and External Validation Of The Chemokine Signaling-...supporting
confidence: 64%
“…Furthermore, we compared the performance of the present signature with those of the other previously reported gene signatures in LUSC. The RMS curve showed that the performance of the present signature was similar to that of the other four signatures (Supplementary Figure S3C) (Huang et al, 2021;Li et al, 2022;Zhai et al, 2022). These results suggest that the CSRG signature can serve as a candidate prognostic biomarker for survival in patients with stage I-III LUSC.…”
Section: Internal and External Validation Of The Chemokine Signaling-...supporting
confidence: 64%
“…e risk prognosis model based on 31 methylation sites of FRGs was superior to the model based on clinicopathologic features in the prediction of 1-, 3-, 5-, and 10-year OS in LUSC. In addition, the accuracy and efficiency of this risk prognosis model were significantly superior to other published models [17,18,[27][28][29][30][31] for LUSC patients.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, the nomogram was tested by proportional hazard assumption to analyze that whether the risk score included in our model was independent prognostic indicators. To evaluate the accuracy and effectiveness of our model, 7 prognostic models of LUSC from published papers [17,18,[27][28][29][30][31] were reviewed and studied with a comparison. Net reclassification index (NRI) and integrated discrimination improvement (IDI) are the common algorithms used to assess the model in recent years [32,33].…”
Section: Construction and Test Of The Nomogrammentioning
confidence: 99%
“…Another study also constructed a prognostic signature based on 9-aging related genes for acute myeloid leukemia [ 26 ]. Moreover, another bioinformatics study also developed an aging-related signature, which had a good performance in risk stratification and prognosis prediction in lung squamous carcinoma [ 27 ].…”
Section: Discussionmentioning
confidence: 99%